Excessive daytime sleepiness is associated with impaired antibody response to influenza vaccination in older male adults - Quach, Huy Quang; Warner, Nathaniel D.; Ovsyannikova, Inna G.; Covassin, Naima; Poland, Gregory A.; Somers, Virend K.; Kennedy, Richard B. (Frontiers in cellular and infection microbiology, 2023)
The reduced effectiveness of standard-dose influenza vaccines in persons ≥65 years of age led to the preferential recommendation to use high-dose (HDFlu) or MF59-adjuvanted (MF59Flu) vaccines for this age group. Sleep is an important modulator of immune responses to vaccines and poor sleep health is common in older adults. However, potential effects of poor sleep health on immune responses to influenza vaccination in older adults remain largely unknown. We conducted a cohort study of 210 healthy participants age ≥65 years, who received either seasonal high-dose (HDFlu) or MF59-adjuvanted (MF59Flu) influenza vaccine. We assessed sleep characteristics in this cohort by standardized questionnaires and measured the antibody titer against influenza A/H3N2 virus in serum of study participants by hemagglutination inhibition assay on the day of immunization and 28 days thereafter. We then assessed the association between sleep characteristics and antibody titers. Our results demonstrated that male, but not female, study participants with excessive daytime sleepiness had an impaired influenza A/H3N2-specific antibody response at Day 28 post-vaccination. No other associations were found between antibody titer and other sleep characteristics, including sleep quality and obstructive sleep apnea. Our results provide an additional and easily measured variable explaining poor vaccine effectiveness in older adults. Our results support that gaining sufficient sleep is a simple non-vaccine interventional approach to improve influenza immune responses in older adults. Our findings extend the literature on the negative influence of excessive daytime sleepiness on immune responses to influenza vaccination in older male adults.